The 2NS Translocation from Aegilops ventricosa Confers Resistance to the Triticum Pathotype of Magnaporthe oryzae. Issue 3 (1st May 2016) - Cruz, C.D.; Peterson, G.L.; Bockus, W.W.; Kankanala, P.; Dubcovsky, J.; Jordan, K.W.; Akhunov, E.; Chumley, F.; Baldelomar, F.D.; Valent, B.
Abstract : Wheat blast is a serious disease caused by the fungus Magnaporthe oryzae ( Triticum pathotype) (MoT). The objective of this study was to determine the effect of the 2NS translocation from Aegilops ventricosa (Zhuk.) Chennav on wheat head and leaf blast resistance. Disease phenotyping experiments were conducted in growth chamber, greenhouse, and field environments. Among 418 cultivars of wheat ( Triticum aestivum L.), those with 2NS had 50.4 to 72.3% less head blast than those without 2NS when inoculated with an older MoT isolate under growth chamber conditions. When inoculated with recently collected isolates, cultivars with 2NS had 64.0 to 80.5% less head blast. Under greenhouse conditions when lines were inoculated with an older MoT isolate, those with 2NS had a significant head blast reduction. With newer isolates, not all lines with 2NS showed a significant reduction in head blast, suggesting that the genetic background and/or environment may influence the expression of any resistance conferred by 2NS. However, when near‐isogenic lines (NILs) with and without 2NS were planted in the field, there was strong evidence that 2NS conferred resistance to head blast. Results from foliar inoculations suggest that the resistance to head infection that is imparted by the 2NS translocation does not confer resistance to foliar disease. In conclusion, the 2NS translocation was associated with significant reductions in head blast in both spring and winter wheat.